Efficacy and safety of acitretin monotherapy in children with pustular psoriasis: results from 15 cases and a literature review. (19th May 2018) - Chen, Pingjiao; Li, Changxing; Xue, Rujun; Chen, Huiheng; Tian, Xin; Zeng, Kang; Zhang, Xibao; Liang, Jingyao
Abstract: Background: There is a few evidence-based information regarding the efficacy and safety of acitretin treatment in children with pustular psoriasis (PP). Objective: This study aimed to provide an additional evidence for this field. Methods: A retrospective study was undertaken for 15 children with PP who received acitretin in doses of 0.6–1.0 mg/kg/day for 4–6 weeks, the transition dose of 0.2–0.4 mg/kg/day for 4–6 weeks and maintenance dose of 0.2–0.3 mg/kg/day. Additionally, a literature review on this topic is conducted. Results: Of 15 children with generalized PP (GPP, n  = 10), palmoplantar psoriasis (PPP, n  = 3), and acrodermatitis continua of Hallopeau (ACH, n  = 2), 93.3% (14/15) showed good response, only one case with ACH exhibited moderate response. During the 10–32 months of follow-up, acitrerin monotherapy for children cases with PP overall showed good efficacy and safety. In the literature review, a total of 107 childhood PP cases treated with acitretin in 21 studies were included in the analysis. The clinical effectiveness was obtained in 88.8% (95/107) patients treated with acitretin as monotherapy or combination therapy, and most of cases (92.6%, 100/107) treated by acitretin did not report side effects during the treatment and follow-up of acitretin. Limitation: This study is just included a small sample sizes and no standardized studies were used in the literature. Conclusion: Acitretin therapy for children with PP (monotherapy or combination therapy), all showed a satisfactory therapeutic effect and safety, independent of the short or long-tern therapeutic procedures.